hopen2impov
Junior Member
- Joined
- Aug 4, 2010
- Messages
- 66
MULTIPLY
(x+1/2) (x^2 +4x +1/2)= (x^2 +4x +1/2) +(1/2) (x^2 +4x +1/2)
(x+1/2) (x^2 +4x -1/2)= (x^3 +4x^2 +(x/2) + (x^2 +2x +1/4)
(x+1/2) (x^2 +4x +1/2)= x^3+ (4+1/2)* x^2+(2 +1/2) * x +1/4
(x+1/2) (x^2 +4x +1/2)= x^3+ (9/2)* x^2+ (9/2)* x^2+ (5/2) * x +1/4
(x+1/2) (x^2 +4x +1/2)= (x^2 +4x +1/2) +(1/2) (x^2 +4x +1/2)
(x+1/2) (x^2 +4x -1/2)= (x^3 +4x^2 +(x/2) + (x^2 +2x +1/4)
(x+1/2) (x^2 +4x +1/2)= x^3+ (4+1/2)* x^2+(2 +1/2) * x +1/4
(x+1/2) (x^2 +4x +1/2)= x^3+ (9/2)* x^2+ (9/2)* x^2+ (5/2) * x +1/4